Diagnostic Performances of Different Genome Amplification Assays for the Detection of Swine Vesicular Disease Virus in Relation to Genomic Lineages That Circulated in Italy - Giulia Pezzoni; Dennis Benedetti; Arianna Bregoli; Ilaria Barbieri; Efrem Alessandro Foglia; Santina Grazioli; Emiliana Brocchi (Viruses, 2020)
During the last 25 years, swine vesicular disease (SVD) has occurred in Italy mostly sub-clinically. Therefore, regular testing of fecal samples from suspected holdings and high turnover premises was fundamental to identifying virus circulation and to achieve SVD eradication. In this study, we evaluated diagnostic performances of six genomic amplification methods, using positive fecal samples from 78 different outbreaks (1997–2014), which included different lineages. Comparison of three RT-PCRs, designed to amplify the same 154 nt portion of the gene 3D, demonstrated that a conventional and a real-time based on SYBR Green detection assay showed the highest diagnostic sensitivity, detecting all samples, while a real-time TaqMan-based test missed three cases, owing to two mismatches in the probe target sequence. Diagnostic and analytical specificities were optimal, as 300 negative field samples and other enteroviruses reacted negative. Three further evaluated tests, previously described, were a 3D-targeted reverse transcriptase loop-mediated isothermal amplification (RT-LAMP) and two real-time RT-PCRs targeted on the 5′UTR region. Here, the presence of multiple mismatches in probe and primers reduced the diagnostic performances, and two of the assays were unable to detect viruses from one sub-lineage. These results highlight that the choice of tests using less nucleotide targets significantly contributed to the success of the SVD eradication plan.